The Effectiveness of Quantum Teaching Method in Teaching Reading Comprehension: (A Quantitative research at Madrasah Tsanawiyah Sabilu El-Muhtadin, Pandeglang) - Ahmad Taufik Walid; Abdul Muin; Fitri Hilmiyati (English Education, Linguistics, and Literature Journal, 2023)
The research is conducted based on the statement of problems. The question of this research is how the effectiveness of the quantum teaching method in teaching reading comprehension at Madrasah Tsanawiyah Sabilu El-Muhtadin? to answer the question, the researcher used quantitative research by implementing quasi experimental design as the research method. The population of this study was the students of ninth grade of MTS Sabilu El-Muhtadin Pandeglang. The sample was divided into two groups, namely control group and experimental group. There were 30 students in control group and 30 students in experimental group. The experimental group was taught by using Quantum teaching method and control group was taught without using Quantum teaching method. After conducting the treatments and evaluating both pre-test and post-test have given, the researcher found that there was significant influence of using quantum teaching method to improve reading comprehension. After collecting and calculating the data, the value of tobservation is bigger than ttable. tobservation = 4.5> ttable = 1.67 (5%), so Ho is rejected, and Ha is accepted. In other words, there is significant difference between group which use Quantum teaching method and group which did not use Quantum teaching method.